Trends, prevalence and associated factors of obesity among adults in a rural community in Thailand: serial cross-sectional surveys, 2012 and 2018 - Boonsub Sakboonyarat; Chanyut Pornpongsawad; Tanatip Sangkool; Chidapha Phanmanas; Nithitchaya Kesonphaet; Nirutti Tangthongtawi; Ammiga Limsakul; Ramita Assavapisitkul; Titipatara Thangthai; Patcha Janenopparkarnjana; Pijitra Varodomvitaya; Wichayada Dachoviboon; et al. (BMC, 2020)
Abstract Background Obesity is one principle risk factor increasing the risk of noncommunicable diseases including diabetes, hypertension and atherosclerosis. In Thailand, a 2014 study reported obesity (BMI ≥25 kg/m2) in a Thai population aged ≥15 years was 37.5, 32.9 and 41.8% overall and among males and females, respectively. The study aimed to determine trends in the prevalence of obesity among adults residing in a Thai rural community between 2012 and 2018 and investigate the associations between obesity and behavioral factors. Methods Serial cross-sectional studies were conducted in 2012 and 2018 among adults in Na-Ngam rural community. In 2012 and 2018, all 635 and 627 individuals, respectively, were interviewed using structured questionnaires related to demographics, risk behaviors, comorbidities and arthrometric measurement. Spot urine was collected by participants and obesity was defined as BMI ≥25 kg/m2. The risk factors for obesity were analyzed in the 2018 survey. Results A total of 1262 adults in Na-Ngam rural community were included in the study. The prevalence of obesity was 33.9% in 2012 and 44.8% in 2018 (P < 0.001). The average BMI increased from 23.9 ± 4.2 kg/m2 in 2012 to 25.0 ± 4.52 kg/m2 in 2018 (P < 0.001). Obesity was associated with higher age (AOR 0.99; 95%CI 0.97-0.99), smoking (AOR 0.52; 95%CI 0.28-0.94), instant coffee-mix consumption > 1 cup/week (AOR 1.44; 95%CI 1.02-2.04), higher number of chronic diseases (≥1 disease AOR 1.82; 95%CI 1.01-2.68, > 2 diseases AOR 2.15; 95%CI 1.32-3.50), and higher spot urine sodium level (AOR 1.002; 95%CI 0.99-1.01). Conclusion Our data emphasized that obesity constituted a serious problem among adults residing in a rural community. A trend in significant increase was found regarding the prevalence of obesity and average BMI in the rural community over 6 years. Effective public health interventions should be provided at the community level to reduce BMI. Moreover, modifiable risk factors for obesity should be attenuated to inhibit the progression of metabolic syndrome, noncommunicable diseases and their complications.